Uniqueness for a class of singular quasilinear Dirichlet problem. (August 2020) - Chu, K.D.; Hai, D.D.; Shivaji, R.
Abstract: We prove uniqueness of positive solutions for the problem − Δ p u = λ f ( u ) u α in Ω, u = 0 on ∂ Ω, where p > 1 + α, α ∈ ( 0, 1 ), Ω is bounded domain in R n with smooth boundary ∂ Ω, f : [ 0, ∞ ) → ( 0, ∞ ) is nondecreasing with f ( z ) ∕ z α decreasing for z large, and λ is a large parameter.